A Voltammetric Sensor Based on NiO Nanoparticle-Modified Carbon-Paste Electrode for Determination of Cysteamine in the Presence of High Concentration of Tryptophan - Hassan Karimi-Maleh; Maryam Salimi-Amiri; Fatemeh Karimi; Mohammad A. Khalilzadeh; Mehdi Baghayeri (Journal of Chemistry)
A carbon-paste electrode modified with ferrocenecarboxaldehyde and NiO nanoparticle (NiO/NPs) was used for the sensitive and selective voltammetric determination of cysteamine in the presence of tryptophan. The oxidation of cysteamine at the modified electrode was investigated by cyclic voltammetry (CV), chronoamperometry, and square-wave voltammetry (SWV). The values of the catalytic rate constant () and diffusion coefficient () for cysteamine were calculated. The modified electrode exhibits an efficient electron-mediating behavior together with well-separated oxidation peaks for cysteamine and tryptophan. At the optimum pH of 7.0 in a 0.1 M phosphate buffer solution, the SWV anodic peak currents showed a linear relationship versus cysteamine concentrations in the range of 0.09–300.0 µM and a detection limit of 0.06 µM. Finally, the proposed method was also examined as a selective, simple, and precise electrochemical sensor for the determination of cysteamine in real samples such as urine and capsule.